2022
DOI: 10.3390/healthcare10071188
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Ocular Biometrics as Measured by Ultrasound Biomicroscopy

Abstract: Background: High frequency ultrasonography (ultrasound biomicroscopy; UBM) is an ophthalmic diagnostic tool that can be used to measure the depth of the anterior segment (ASD), the anterior chamber angle (ACA), as well as thicknesses of the iris and the ciliary body (CB). Methods: The anterior segment dimensions and thicknesses were measured by Sonomed 35-MHz. Results: Measurements for 95 eyes from 52 adults were analyzed. The mean and median ASD and ACA were 2.91, 2.92 ± 0.41 mm and 34.1, 34.3 ± 12.1 degrees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Mean ASD was 2.92 mm, and mean ACA was 34.3 degrees. Iris thickness was measured in three places, the root of the iris, the middle of the iris, and the juxtapupillary edge of the iris, with mean measurements of 0.41, 0.51, and 0.71 mm in each location, respectively [ 11 ]. A second study investigating iris thickness found mean thickness at the root of the iris to be 0.41, mean thickness at the middle of the iris to be 0.51, and mean thickness at the juxtapupillary margin to be 0.71 mm [ 12 ].…”
Section: Current Clinical Application Of Ubmmentioning
confidence: 99%
“…Mean ASD was 2.92 mm, and mean ACA was 34.3 degrees. Iris thickness was measured in three places, the root of the iris, the middle of the iris, and the juxtapupillary edge of the iris, with mean measurements of 0.41, 0.51, and 0.71 mm in each location, respectively [ 11 ]. A second study investigating iris thickness found mean thickness at the root of the iris to be 0.41, mean thickness at the middle of the iris to be 0.51, and mean thickness at the juxtapupillary margin to be 0.71 mm [ 12 ].…”
Section: Current Clinical Application Of Ubmmentioning
confidence: 99%